Time synchronization method for wireless sensor networks based on mobile reference nodes - Yu-qiang ZHANG; Jing-sha HE; Jing XU; Bin ZHAO; Fang-bo CAI (Tongxin xuebao)
Most existing time synchronization methods in wireless sensor networks depend on the existence of one or more fixed reference nodes and on the propagation of synchronization messages in the networks.Thus,they often suffer from the disadvantages of high energy consumption and large cumulative error due to multiple layers of communication.To address such issues,a new time synchronization method based on a mobile reference node and the optimal mobile path is proposed.Firstly,the cellular coverage technique is analyzed to identify the optimal synchronization points.Then,the optimal mobile path with minimal length is designed.Finally,an efficient single hop time synchronize mechanism based on multiple timestamps in the MAC layer is presented.Comparison with other methods shows that the proposed method can achieve both higher synchronization accuracy and lower energy consumption.